Applying chorems in the cartographic presentation of barriers to socio-economic development in Poland - Bielecka, Elżbieta; Markowska, Anna; Dukaczewski, Dariusz (Quaestiones Geographicae, 2024)
This paper presents the theoretical axioms of chorems based on cartographic semiotics. Employing geometric and functional elements and the cartographic state-of-the-art, a regional, national chorem has been created. This chorem portrays the barriers to Polish regional development. It depicts the main development centres, industrial areas and zones of constraint created by the country’s external borders, borders of the European Union (EU) and major rivers. The paper also defines chorematic affordance as the dynamic and processual feedback between the domain expert and the geographical or socio-economic processes. The elaborate chorematic diagram contributes not only to cartographers and geographers but also to public administration dealing with sustainable development, as it is intricately tied to regional development, emphasising the crucial importance of effective land management, equitable land distribution and sustainable development.